Predictive factors of postoperative physical performance impairment among patients with brain tumor surgery: A predictive-correlation study - Panruy, Khemmarat; Hengyotmark, Arunee; Sriamornrattanakul, Kitiporn; Itthimathin, Parunut (Science, Engineering and Health Studies, 2025)
Impaired physical performance in patients following brain tumor surgery can reflect the quality of care. For this reason, contributing factors should be identified and managed. This study aimed to investigate the predictive power of frailty, nutritional status, and surgical complexity over postoperative physical performance impairment in patients undergoing brain tumor surgery by using a cross-sectional design. The sample included 125 patients aged 18 years and over who had undergone brain tumor surgery. Data were collected using the modified frailty index, the nutrition alert form, the Milan complex scale, and the Karnofsky performance status scale to compare physical performance before and 30 days after surgery. A decrease of 10 points or on the scale indicated physical impairment. Descriptive statistics and binary logistic regression were used for data analysis. Postoperative brain tumor surgery patients who had high frailty, moderate or severe malnutritional status, and tumor removal complexity were likely to have a higher risk of impaired physical performance than other groups. Health issues such as frailty and malnourishment should be corrected in patients before surgery and preparation should be made for perioperative care in patients with surgical complexities to prevent physical impairment.